Do Higher Education Institutions Foster Social Entrepreneurship? Curriculum Analysis at the University of Valencia - Estefanía López Requena (Research Synergy Foundation, 2025)
Universities play a crucial role in fostering entrepreneurial skills to support students’ professional integration. However, in an increasingly complex and dehumanised socio-economic and political context, it is essential to evaluate whether higher education addresses the social dimension of entrepreneurship. This study explores the extent to which social entrepreneurial competencies are embedded in undergraduate curricula at the University of Valencia (Spain). A qualitative content analysis was conducted on 60 degrees verification reports, using proxy indicators to identify the presence of such competencies. Findings reveal a limited and uneven integration of social entrepreneurship skills, with significant variation across academic disciplines.